Los pictogramas en el desarrollo del lenguaje en los niños de educación inicial - Lema Gallo, Jessica Andrea (2017)
Education is considered from the second year of basic education, which is when children should learn to read and write; But it is also necessary to know what happens in the initial level of the Educational Unit "Manuelita Sáenz" of the city Ignacio Flores, Ahspacruz neighborhood belonging to the Latacunga and for which the following research topic was raised: "the pictograms in the language development in children of initial education ". They are established in this stage of education with the children of five years; Because one of the primary activities of nursery teachers is to work on the reading and writing skills of children; As they still do not know how to read and write like the others, it is very important that they work with graphics, for the primary decoding they carry out. Interview questionnaires were designed and applied to the Mr. Principal and teacher of the institution, a survey of parents was also structured and an observation sheet was given to the children, in order to have direct information about what happened in the classroom. It is evidenced that more than half of parents do not support the development of the language of their children being this 76.92%, just like 100% of parents do not know about reading based on pictograms in the same....